The Politics of Climate Change and Uncertainty in India - Mehta, Lyla; Adam, Hans Nicolai; Srivastava, Shilpi (Pathways to Sustainability, 2022)
This book brings together diverse perspectives concerning uncertainty and climate change in India. Uncertainty is a key factor shaping climate and environmental policy at international, national and local levels. Climate change and events such as cyclones, floods, droughts and changing rainfall patterns create uncertainties that planners, resource managers and local populations are regularly confronted with. In this context, uncertainty has emerged as a "wicked problem" for scientists and policymakers, resulting in highly debated and disputed decision-making. The book focuses on India, one of the most climatically vulnerable countries in the world, where there are stark socio-economic inequalities in addition to diverse geographic and climatic settings. Based on empirical research, it covers case studies from coastal Mumbai to dryland Kutch and the Sundarbans delta in West Bengal. These localities offer ecological contrasts, rural-urban diversity, varied exposure to different climate events, and diverse state and official responses. The book unpacks the diverse discourses, practices and politics of uncertainty and demonstrates profound differences through which the "above", "middle" and "below" understand and experience climate change and uncertainty. It also makes a case for bringing together diverse knowledges and approaches to understand and embrace climate-related uncertainties in order to facilitate transformative change. Appealing to a broad professional and student audience, the book draws on wide-ranging theoretical and conceptual approaches from climate science, historical analysis, science, technology and society studies, development studies and environmental studies. By looking at the intersection between local and diverse understandings of climate change and uncertainty with politics, culture, history and ecology, the book argues for plural and socially just ways to tackle climate change in India and beyond.